2021
DOI: 10.1101/2021.08.27.21262356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19-associated hospitalizations among vaccinated and unvaccinated adults ≥18 years – COVID-NET, 13 states, January 1 – July 24, 2021

Abstract: Background: As of August 21, 2021, >60% of the U.S. population aged ≥18 years were fully vaccinated with vaccines highly effective in preventing hospitalization due to Coronavirus Disease-2019 (COVID-19). Infection despite full vaccination (vaccine breakthrough) has been reported, but characteristics of those with vaccine breakthrough resulting in hospitalization and relative rates of hospitalization in unvaccinated and vaccinated persons are not well described, including during late June and July 2021 when… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…This finding is consistent with previous studies suggesting that fully vaccinated people with breakthrough infections tend to have attenuated viral load, fewer symptoms, and shorter duration of illness, although severe outcomes can still occur. 8 35 36 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies suggesting that fully vaccinated people with breakthrough infections tend to have attenuated viral load, fewer symptoms, and shorter duration of illness, although severe outcomes can still occur. 8 35 36 …”
Section: Discussionmentioning
confidence: 99%
“…were unvaccinated during the study timeframe. [23][24][25] A study of fully vaccinated mAb-treated patients reported that the number needed to treat (NNT) to prevent one hospitalization was 225 among the lowestrisk patients compared to a NNT of 4 among the highest risk patients. 26 Our results also suggest that a "watch and wait" approach is appropriate for fully vaccinated patients with fewer comorbidities versus an immediate test and treat approach for the highest risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 In the USA, large numbers of adults are fully vaccinated, large numbers are unvaccinated, and systematic comparisons between them are ongoing. Recent reports of large US studies (one from the US CDC's COVID-NET 13 and two from major health maintenance organisations 14,15 ) demonstrate the continued high efficacy of full vaccination against severe disease or hospitalisation.…”
mentioning
confidence: 99%